The Effect of Tato and DER on Stock Prices, with ROA as a Mediator, on the Jakarta Islamic Index - Muhammad Ulil Abror; Acong Dewantoro Marsono (Publikasi Indonesia, 2025)
This research aims to analyze the effect of the operational efficiency ratio (TATO) and the capital structure ratio (DER) on the stock prices of companies listed in the Jakarta Islamic Index (JII), with the profitability ratio (ROA) as an intervening variable. The research covers the period from 2020 to 2025 and employs a purposive sampling technique. Data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 4.0. The results of the hypothesis testing indicate that: (1) TATO has a positive and significant effect on stock price (coefficient = 0.272; t = 2.523; p = 0.012); (2) DER has a negative and significant effect on stock price (coefficient = -0.289; t = 3.171; p = 0.002); (3) ROA has a positive and significant effect on stock price (coefficient = 0.251; t = 3.492; p = 0.000); (4) TATO positively affects ROA (coefficient = 0.217; t = 2.918; p = 0.004); (5) DER negatively affects ROA (coefficient = -0.288; t = 4.543; p = 0.000); (6) ROA mediates the effect of TATO on stock price (coefficient = 0.054; t = 2.094; p = 0.036); and (7) ROA mediates the effect of DER on stock price (coefficient = -0.072; t = 2.592; p = 0.010). The adjusted R-square value for stock price is 0.158. These findings demonstrate that operational efficiency, capital structure, and profitability ratios significantly influence the market value of Islamic stocks, both directly and through mediation mechanisms.